Strategic directions of the sustainable development for the city of Kremenchuk in Ukraine - Trunina, Iryna; Pryakhina, Katerina; Latyshev, Kostyantyn; Skrebcova, Ksenia (Strategiczne kierunki zrównoważonego rozwoju miasta Krzemieńczuk na Ukrainie, 2020)
The article addresses the theoretical aspects of sustainable development; the content of methodological approaches to the assessment of sustainable city development is determined, the system of evaluation of sustainable city development is characterized, the dynamics of economic, social and ecological development of Kremenchuk are analyzed and recommendations for improving the sustainable development of the city are developed. The purpose of the research was to develop measures to improve the economic, social, environmental components of sustainable development of the Ukrainian industrial city of Kremenchuk
Biblioteka Regionalisty, 2020, Nr 20, s. 180-193
Keywords: local self-government; sustainable urban development concept; Ukraine; Kremenchuk (Ukraine); samorząd; koncepcja zrównoważonego rozwoju; zrównoważony rozwój miast; Ukraina; Krzemieńczuk (Ukraina)